Maximum Tolerated Volume and Plasma Acylated Ghrelin Levels after Drink Tests in Patients with Functional Dyspepsia - Suharjo B Cahyono; Neneng Ratnasari; Putut Bayupurnama; Nurdjanah S (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Background: Impaired gastric accommodation and visceral hypersensitivity are major pathophysiological mechanism in functional dyspepsia (FD). Ghrelin, as gut hormone, may play a pathophysiological role in functional dyspepsia. Nutrient drink test was developed to assess impaired gastric accommodation in FD patients.  The aims of this study are to compare maximum tolerated volume, postprandial symptoms and acylated ghrelin levels between dyspepsia functional patients and healthy subjects as controls.Method: A cross sectional study was conducted from July 2014 to November 2014, at Sardjito General Hospital, Yogyakarta. Twenties functional dyspepsia  patients and 20 healthy subjects ingested  nutrient drink tests (Ultra Milk contain 0.6 kcal/mL). The maximum tolerated volume was recorded. After ingested maximal tolerated volume, nausea, bloating and pain were rated using visual analogue scales (VAS) with 100 mm lines. The levels of acylated ghrelin was recorded before and 30 minutes after maximal drinking.Results: The demographic characteristics (age, sex, and body mass index) between dyspepsia patients and healthy subjects were compared. Patients with functional dyspepsia ingested 600 (350–1000) mL and healthy subjects ingested 1375 (1000–1900) mL (p 0.001). The total symptom scores were higher in dyspepsia patients compared healthy subjects; 215 (110–350)  vs. 75 (50–120)  (p 0,001). The fasting plasma levels of acylated ghrelin (20.65 : 2 – 31.37 pg/mL) in FD patients were  significantly lower than healthy subjects (30.61 : 2 – 251.19 pg/mL) (  p = 0.012). Conclusion: Patients with functional dyspepsia ingested significantly lower volume and significantly have higher score symptoms than healthy subjects. The fasting plasma levels of acylated ghrelin in functional dyspepsia patients were  significantly lower  than healthy subjects.